2017
DOI: 10.5826/dpc.0703a04
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of plantar warts with intralesional bleomycin and electroporation: pilot prospective study

Abstract: BackgroundNumerous studies have been performed to evaluate the efficacy of intralesional bleomycin for the treatment of warts with inconsistent result. Nevertheless, it is well known that the cytotoxicity of bleomycin can be enhanced in vivo by 300 to 700-fold by electroporation.Objective and MethodsIn this article, we present an interventional, one-center, prospective case series, clinical trial of the effectiveness of intralesional bleomycin combined with electroporation for the treatment of plantar warts, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 15 publications
4
23
0
2
Order By: Relevance
“…The cure rate was superior in the group for which electrochemotherapy associated with intralesional use of bleomycin was performed (78% vs. 16%), and this difference was statistically significant. Similar to the data found in our study, no systemic side‐effects were observed, with only erythema and oedema being reported as local side‐effects …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The cure rate was superior in the group for which electrochemotherapy associated with intralesional use of bleomycin was performed (78% vs. 16%), and this difference was statistically significant. Similar to the data found in our study, no systemic side‐effects were observed, with only erythema and oedema being reported as local side‐effects …”
Section: Discussionsupporting
confidence: 91%
“…Similar to the data found in our study, no systemic side-effects were observed, with only erythema and oedema being reported as local side-effects. 46 We observed that the side-effects were more frequently observed in the electrochemotherapy group (pain, haemorrhagic necrosis, onycholysis, infectious process and reflex sympathetic dystrophy). Although more frequent and intense, the side-effects in the electrochemotherapy group were tolerable for patients, there were no long-term sequelae, and no systemic adverse effects were observed.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…There is no concensus about the procedure for application, the frequency of application, concentration, and dosing schedule ending up with bleomycin being level 1 strength of evidence in treating warts. 11 In the current study, we used intralesional bleomycin with single and multiple puncture techniques induced by microneedling. Among the first to use the multipuncture technique for different types of warts.…”
Section: Discussionmentioning
confidence: 99%